The Idea of Implementing a District Election System as an Alternative for Simplifying Political Parties in Indonesia - Josefh Perangin Angin; Fifiana Wisnaeni (DE LEGA LATA: JURNAL ILMU HUKUM, 2022)
Political parties and general elections are elements that cannot be separated from the life of a country, because they can be used as tools and solutions for the change and progress of a nation. However, they can be a tool for state change if they can run in harmony and dont cause problems. Indonesia is a country that cannot be separated from Political Parties and Election Culture. Political parties have existed since the Dutch colonial era until now. Meanwhile, the electoral system was only known in Indonesia in the era of parliamentary democracy, where the plan was to elect a parliament nominated by a political party. However, the development of Indonesian political parties has harmed the lives of Indonesia, such as fragmentation between political parties, etc. Because of that, the government in the colonial era, new order until now, create policies to overcome this. One of the policies taken and proven to solve is the simplification of political parties by implementing a district election system. This system was introduced and used during the New Order era. This system is used as an alternative because the system is simple and able to overcome problems with the simplification method of political parties